2021
DOI: 10.1136/injuryprev-2020-044038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for road traffic injuries and mortalities in Ethiopia: systematic review and meta-analysis

Abstract: BackgroundRoad traffic injuries, which are responsible for premature deaths and functional losses, are the leading causes of unintentional injuries in Ethiopia. As most studies on road traffic injuries, so far, have been either local or regional, it is believed that combining the regional or local data to get nationally representative information could help programme implementers in setting priorities.ObjectiveThe aim of this review was to estimate the proportion of road traffic injuries, mortality and risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The literature review yielded 15 studies that potentially used nationally representative data sources on the incidence of road traffic injuries (online supplemental appendix 1 table A1). 15–29 However, full-text evaluations revealed that the cited data sources in these studies were either not representative of the population (eg, were sub-national, or from surveillance at selected hospitals) or referenced the DHS-2016, which had been identified in our review of primary data sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review yielded 15 studies that potentially used nationally representative data sources on the incidence of road traffic injuries (online supplemental appendix 1 table A1). 15–29 However, full-text evaluations revealed that the cited data sources in these studies were either not representative of the population (eg, were sub-national, or from surveillance at selected hospitals) or referenced the DHS-2016, which had been identified in our review of primary data sources.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we conducted Snowball searches by scanning reference lists of published reports retrieved from the processes above. In particular, the reference lists of two systematic literature reviews were scanned for potential data sources 15 16…”
Section: Methodsmentioning
confidence: 99%
“…3 Drunk driving and lack of driving experience as well as lighting condition were associated with road traffic accidents. 4 Vehicle-related risk factors of traffic accident included unsafe car modifications and no safety equipment. 5 Economic burden of traffic accidents can be measured through loss of productivity caused by accident-related injuries and deaths.…”
Section: Introductionmentioning
confidence: 99%
“…15 Road traffic injuries are the major cause of injuries, making up 29% of all traumas. 16 Ethiopia has been training emergency professionals since 2010, 17 but there is no ambulatory emergency care system to provide pre-hospital emergency service in the community, except for infrequent ambulance transport. 18 Previous studies reported the absence of pre-hospital emergency services, 19 poor road infrastructure, and limited transportation access as the causes for delays in definitive care for trauma victims.…”
Section: Introductionmentioning
confidence: 99%